Hubungan Bauran Pemasaran (7P) dengan Keputusan Pembelian Konsumen Kopi Kenangan Salatiga - Yoktan, Excel Dionisiyus; Nuswantara, Bayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to identify consumer characteristics and analyze the relationship between marketing mix (7P) and consumer purchasing decisions at Kopi Kenangan Salatiga. Data were collected by survey, using questionnaires to 96 purposively selected respondents. Data were analyzed using Spearman rank correlation. The results showed that Kopi Kenangan's main market segments are young people and women; all elements of the marketing mix (7P) consisting of product, price, place, promotion, people, process, and physical evidence have a significant relationship with consumer purchasing decisions at Kopi Kenangan Salatiga. Based on these results, Kopi Kenangan is advised to strengthen its marketing strategy especially on the aspects of physical evidence, price, and product to increase consumer attraction and loyalty in Salatiga.